Surface area of a square pyramid is the area of the base + 4 times the area of one of the slanted sides.
Area of base = side length * side length
Area of side = (1/2) * side length * slant height
Don't forget that you have to multiply the area of the side by 4!
Step 1: 12 x 12 = 144
Step 2: 12 x 20 = 240 divided by 2 = 120
Step 3: 144 + 120 x 4
True. If they never intersect then they must have the same slope and are parallel
Well, kid all you have to do is add like terms and place the subjected terms in alphabetical order.
1. (6y-2c+2)+(-3y+4c)
2. 6y + - 3y = 3y
3. -2c+4c =2c
4. the positive in the first set of parenthesis has to term other than its number by itself. (so it remains alone and only positive 2)
5. take all the separate term answers and add them into a complete expression- 3y + 2c + 2: and that is all